The effects of transport regulation on the oil market. Does market power matter? - Snorre Kverndokk; Knut Einar Rosendahl (Statistics Norway, Research Department, 2010)
Popular instruments to regulate consumption of oil in the transport sector include fuel taxes, biofuel requirements, and fuel efficiency. Their impacts on oil consumption and price vary. One important factor is the market setting. We show that if market power is present in the oil market, the directions of change in consumption and price may contrast those in a competitive market. As a result, the market setting impacts not only the effectiveness of the policy instruments to reduce oil consumption, but also terms of trade and carbon leakage. In particular, we show that under monopoly, reduced oil consumption due to increased fuel efficiency will unambiguously increase the price of oil.
Keywords: D42; Q54; R48; 330; Transport regulations; oil market; monopoly; terms-of-trade effects; carbon leakage